Learning Media Innovation to Improve Learning Motivation in Physical Education on Fundamental Movement Material - Fajar Advis Wahyudin; Mochamad Ridwan; Muchamad Arif Al Ardha (Jurnal Pendidikan Jasmani (JPJ), 2026)
This study aims to determine the effect of the implementation of GASPOL (Fun Movement While Playing Sports) learning media innovation on students' learning motivation in Physical Education, Sports, and Health (PJOK) learning on fundamental movement material. The study used a quantitative approach with a weak experimental design through a one-group pretest–posttest design model. The subjects were 31 second-grade elementary school students in Gresik Regency. The data collection instrument was a learning motivation questionnaire using a Likert scale that had been tested for validity and reliability. Data analysis was carried out using descriptive statistics, normality tests, and paired sample t-tests. The results showed an increase in students' learning motivation after the implementation of GASPOL media, indicated by an increase in the average score from 69.64 in the pretest to 75.18 in the posttest, with a percentage increase of 7.96%. In addition, a decrease in the standard deviation value in the posttest indicates that students' learning motivation has become more evenly distributed. Thus, the GASPOL learning media has been proven effective in increasing students' learning motivation in PJOK learning on fundamental movement material and can be used as an alternative learning media that is innovative, active, and fun in elementary schools.